Everest: Towards a Verified, Drop-In Replacement of HTTPS - Bhargavan, Karthikeyan; Bond, Barry; Delignat-Lavaud, Antoine; Fournet, Cédric; Hawblitzel, Chris; Hritcu, Catalin; Ishtiaq, Samin; Kohlweiss, Markulf; Leino, Rustan; Lorch, Jay; Maillard, Kenji; Pang, Jinyang; et al. (SNAPL 2017 - 2nd Summit on Advances in Programming Languages, 2017)
The HTTPS ecosystem is the foundation on which Internet security is built. At the heart of this ecosystem is the Transport Layer Security (TLS) protocol, which in turn uses the X.509 public-key infrastructure and numerous cryptographic constructions and algorithms. Unfortunately, this ecosystem is extremely brittle, with headline-grabbing attacks and emergency patches many times a year. We describe our ongoing efforts in Everest, a project that aims to build and deploy a verified version of TLS and other components of HTTPS, replacing our infrastructure with proven, secure software. Aiming both at full verification and usability, we conduct high-level code-based, game-playing proofs of security on cryptographic implementations that yield efficient, deployable code, at the level of C and assembly. Concretely, we use F*, a dependently typed language for (meta-)programming and proving at a high level, while relying on low-level DSLs embedded within F* for programming low-level components when necessary for performance and, sometimes, side-channel resistance. To compose the pieces, we compile all our code to source-like C and assembly, suitable for audit and deployment by independent security experts. Our main results so far include (1) the design of Low*, a subset of F* designed for C-like imperative programming but with high-level verification suppport, and KreMLin, a compiler that extracts Low* programs to C; (2) an implementation of the TLS-1.3 record layer in Low*, together with a proof of its concrete cryptographic security; (3) Vale, a new DSL for verified assembly language, and several optimized cryptographic algorithms proven functionally correct. In an early deployment, all our verified software is integrated and deployed within libcurl, a widely used library of networking protocols. In cooperation with: INRIA Paris, Team Prosecco; MIT, CSAIL.